Development of Accounting Learning through An Internship Program - Lutfi Zulkarnain; Endin Mujahidin (Sultan Publisher, 2023)
Universities have an important role in preparing superior human resources, one of which is in the field of accounting. Internships can be a learning method that can be used to improve the competency of human resources. However, what kind of internship activities can provide more learning than what students get in lectures, especially internship activities in the accounting field? Therefore, this article aims to examine internship activities that can improve student competency, especially students majoring in accounting. This article was created using the literature method with a descriptive analysis approach. The results of the study show that there are several internship programs that can be carried out in the accounting field. However, the competencies to be achieved tend to only be competencies in the cognitive and psychomotor domains. Meanwhile, competence in the affective domain, especially attitudes as a sharia accountant who has a code of ethics, tends to be less explored in sharia accounting internship programs. Therefore, it is necessary to add converted courses by adding business and professional ethics courses in the internship activities of students majoring in accounting so that competence in the affective domain can be achieved.